Cryptic dioecy in Mussaenda pubescens (Rubiaceae): a species with stigma-height dimorphism - Li, Ai-Min (Oxford University Press, 2010)
BACKGROUND AND AIMS: Evolutionary transitions from heterostyly to dioecy have been proposed in several angiosperm families, particularly in Rubiaceae. These transitions involve the spread of male and female sterility mutations resulting in modifications to the gender of ancestral hermaphrodites. Despite sustained interest in the gender strategies of plants, the structural and developmental bases for transitions in sexual systems are poorly understood. METHODS: Here, floral morphology, patterns of fertility, pollen-tube growth and floral development are investigated in two populations of the scandent shrub Mussaenda pubescens (Rubiaceae), native to southern China, by means of experimental and open-pollinations, light microscopy, fluorescence microscopy and scanning electron microscopy combined with paraffin sectioning. KEY RESULTS: Mussaenda pubescens has perfect (hermaphroditic) flowers and populations with two style-length morphs but only weak differentiation in anther position (stigma-height dimorphism). Experimental pollinations demonstrated that despite morphological hermaphroditism, the species is functionally dioecious. The long-styled (L) morph possesses sterile pollen and functions as a female, whereas the short-styled (S) morph is female sterile and functions as a male. Self- and intra-morph pollinations of the S-morph were consistent with those expected from dimorphic incompatibility. The two populations investigated were both S-morph (male) biased. Investigations of early stages of floral development indicated patterns typical of hermaphroditic flowers, with no significant differences in organ growth between the floral morphs. Meiosis of microspore mother cells was of the simultaneous type with tetrads isobilateral in shape. The tapetal cells in anther walls of the L-morph became vacuolized during meiosis I, ahead of the uninucleate microspore stage in the S-morph. In the L-morph, the microspore nucleus degenerated at the tetrad stage resulting in male sterility. Microsporogenesis and male gametophyte development was normal in the S-morph. Failure in the formation of megaspore mother cells and/or the development of megagametophytes resulted in female sterility in the S-morph, compared with normal megasporogenesis in the L-morph. CONCLUSIONS: In M. pubescens, cryptic dioecy has evolved from stigma-height dimorphism as a result of morph-specific sterility mutations.